en - Wahyu Sudewi, Putu (e-Journal of Linguistics; Vol 15 No 1 (2021): ejl-January, 2020)
The Minister of Education and Culture, issued Circular Number 4 of 2020 concerning the Implementation of Education in Emergency Coronavirus (Covid-19), one of which emphasized that online learning (distance), was carried out to provide meaningful learning experiences for students, without being burdened by the demands of completing all curriculum achievements for class and graduation. Online / distance learning is focused on increasing students' understanding of the corona virus and the Covid-19 outbreak. E-Learning is the best choice for education in the midst of the Covid-19 outbreak. However, in Indonesia, not all students are familiar with the E-Learning system so this has become a new thing that requires adaptation. This research aimed at knowing the students’ perceptions toward E -learning during Covid-19 pandemic at Sulawesi Barat University . This descriptive research was done by questionnaire in collecting the data. The source of the data was students of English Education Department Faculty of Teacher Training and Education Sulawesi Barat University. The result of the analysis shows that there were 73 .7 % of students felt the lecturer explained the material well , 84 , 2 % of students expressed the material provide based on semester learning plan, and 75, 4 % of students expressed e-learning was effective , 77.2% of students said that their ability has increase learning in E-learning and 64.9 % of students expressed lecturer conducted question and answer activities. As a result, the students’ perceptions of e-learning were gets positive perception because it is flexible and effective. Meanwhile, its flexibility made some students motivated but some were being lazy in doing it and choose to suspend the assignments.